Novel Synthetic, Host-defense Peptide Protects Against Organ Injury/Dysfunction in a Rat Model of Severe Hemorrhagic Shock. Issue 2 (August 2018) - Yamada, Noriaki; Martin, Lukas B.; Zechendorf, Elisabeth; Purvis, Gareth S. D.; Chiazza, Fausto; Varrone, Barbara; Collino, Massimo; Shepherd, Joanna; Heinbockel, Lena; Gutsmann, Thomas; Correa, Wilmar; Brandenburg, Klaus; et al.
Abstract : Objective: To evaluate (1) levels of the host-defense/antimicrobial peptide LL-37 in patients with trauma and hemorrhagic shock (HS) and (2) the effects of a synthetic host-defense peptide; Pep19-4LF on multiple organ failure (MOF) associated with HS. Background: HS is a common cause of death in severely injured patients. There is no specific therapy that reduces HS-associated MOF. Methods: (1) LL-37 was measured in 47 trauma/HS patients admitted to an urban major trauma center. (2) Male Wistar rats were submitted to HS (90 min, target mean arterial pressure: 27–32 mm Hg) or sham operation. Rats were treated with Pep19-4LF [66 (n = 8) or 333 μg/kg · h (n = 8)] or vehicle (n = 12) for 4 hours following resuscitation. Results: Plasma LL-37 was 12-fold higher in patients with trauma/HS compared to healthy volunteers. HS rats treated with Pep19-4LF (high dose) had a higher mean arterial pressure at the end of the 4-hour resuscitation period (79 ± 4 vs 54 ± 5 mm Hg) and less renal dysfunction, liver injury, and lung inflammation than HS rats treated with vehicle. Pep19-4LF enhanced (kidney/liver) the phosphorylation of (1) protein kinase B and (2) endothelial nitric oxide synthase. Pep19-4LF attenuated the HS-induced (1) translocation of p65 from cytosol to nucleus, (2) phosphorylation of IκB kinase on Ser 176/180, and (3) phosphorylation of IκBα on Ser 32/36 resulting in inhibition of nuclear factor kappa B and formation of proinflammatory cytokines. Pep19-4LF prevented the release of tumor necrosis factor alpha caused by heparan sulfate in human mononuclear cells by binding to this damage-associated molecular pattern. Conclusions: Trauma-associated HS results in release of LL-37. The synthetic host-defense/antimicrobial peptide Pep19-4LF attenuates the organ injury/dysfunction associated with HS. Abstract : Supplemental Digital Content is available in the text